Soil and Tissue Testing and Interpretation for Florida Turfgrasses - Jerry B. Sartain (EDIS, 2009)
Revisd! SL-181, an 8-page fact sheet by J.B. Sartain, provides essential basic facts about the nutritional requirements of turfgrasses, the properties of fertilizer and liming materials, and how to use them to maintain sufficient nutrient levels through soil and tissue analysis. Published by the UF Department of Soil and Water Science, October 2008.